2008
DOI: 10.1162/pres.17.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Training via Vibrotactile Arrays

Abstract: What is often missing from many virtual worlds and training simulations is a physical sense of the confinement and constraint of the virtual environment. We present a method for providing localized cutaneous vibratory feedback to the user's right arm. We created a sleeve of tactors linked to a real-time human model; the tactors activate to apply sensation to the corresponding body area. The hypothesis is that vibrotactile feedback to body areas provides the wearer sufficient guidance to assume correct body con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 12 publications
0
36
0
3
Order By: Relevance
“…One recent implementation of this spatially distributed contact feedback approach was done by Bloomfield and Badler [4], who created a tactile sleeve embedded with vibrotactile actuators and optical motion-tracking markers. Subjects reached within 3D virtual puzzles while trying to avoid collisions with the walls.…”
Section: Tactile Feedback For Motion Guidancementioning
confidence: 99%
See 1 more Smart Citation
“…One recent implementation of this spatially distributed contact feedback approach was done by Bloomfield and Badler [4], who created a tactile sleeve embedded with vibrotactile actuators and optical motion-tracking markers. Subjects reached within 3D virtual puzzles while trying to avoid collisions with the walls.…”
Section: Tactile Feedback For Motion Guidancementioning
confidence: 99%
“…We chose to use tactile feedback derived from joint angle errors to guide the subject to target arm configurations, as we believe this may be an intuitive motion domain. This choice is similar to Lieberman and Breazeal [14] and is in contrast to the Cartesian collision paradigm chosen by Bloomfield and Badler [4]. For each joint we define an angular tolerance, ฮธ Tolerance , which is used to determine whether the current pose is close enough to the goal.…”
Section: Tactile Feedback Algorithmmentioning
confidence: 99%
“…In particular, the potential of vibrotactile feedback to enhance motor learning has been shown in a number of user studies [3,5,7]. Spelmezan et al [6] used patterns of vibrations across the body to indicate to participants different actions to take whilst snowboarding, reporting faster reaction times than the same instructions given verbally; Lieberman and Breazeal [5] showed that the addition of vibrotactile feedback improved participants' abilities to mimic the joint angles of a moving arm shown on screen; and Bloomfield and Badler [3] employed vibrotactile feedback to teach aspects of karate and found that participants improved significantly after receiving vibrotactile feedback.…”
Section: Introductionmentioning
confidence: 99%
“…[4] , ๋“œ๋Ÿผ ๋ฆฌ ๋“ฌ ์—ฐ์ฃผ [5] , ์—ฐ์ฃผ ์†๋„ ์กฐ์ ˆ [6] , ๋ณดํ–‰ ์†๋„ ์กฐ์ ˆ [7] , ์Šค๋…ธ์šฐ ๋ณด ๋”ฉ ์ž์„ธ [8] ๋“ฑ ๋‹ค์–‘ํ•œ ๊ธฐ๋Šฅ์— ๋Œ€ํ•ด ์‹œ๋„๋˜์—ˆ๋‹ค. ์ง€์‹œ๋ฟ๋งŒ ์•„ ๋‹ˆ๋ผ, ์ง„๋™ ์ž๊ทน์„ ํ†ตํ•œ ๋ณด๊ฐ•์  ํ”ผ๋“œ๋ฐฑ์œผ๋กœ ํŒ”์˜ ์ž์„ธ [9,10] , ๋ณดํ–‰ ํŒจํ„ด [11] , ๋ฐ”์ด์˜ฌ๋ฆฐ ์—ฐ์ฃผ ๋™์ž‘ ๋ฐ ์ž์„ธ [12] ๋ฅผ ๊ต์ •ํ•œ ์—ฐ ๋ฌธ์— ์‹ฌ๋„ ์žˆ๊ฒŒ ์ •๋ฆฌ๋˜์–ด ์žˆ๋‹ค [13,14] . ๊ธฐ์กด์˜ ์ด‰๊ฐ ์šด๋™ ํ•™์Šต ์—ฐ๊ตฌ ์ค‘, ์†Œ์ˆ˜์˜ ๋ฌธํ—Œ๋“ค๋งŒ์ด ์ด‰๊ฐ ๊ต์œก์˜ ํšจ๊ณผ๋ฅผ ์‹œ๊ฐ ๋˜๋Š” ์ฒญ๊ฐ ๊ต์œก๊ณผ ์ •๋Ÿ‰์ ์œผ๋กœ ๋น„๊ตํ•˜์˜€๋‹ค [6,8,10,[15][16][17] .…”
unclassified
“…์ง€์‹œ๋ฟ๋งŒ ์•„ ๋‹ˆ๋ผ, ์ง„๋™ ์ž๊ทน์„ ํ†ตํ•œ ๋ณด๊ฐ•์  ํ”ผ๋“œ๋ฐฑ์œผ๋กœ ํŒ”์˜ ์ž์„ธ [9,10] , ๋ณดํ–‰ ํŒจํ„ด [11] , ๋ฐ”์ด์˜ฌ๋ฆฐ ์—ฐ์ฃผ ๋™์ž‘ ๋ฐ ์ž์„ธ [12] ๋ฅผ ๊ต์ •ํ•œ ์—ฐ ๋ฌธ์— ์‹ฌ๋„ ์žˆ๊ฒŒ ์ •๋ฆฌ๋˜์–ด ์žˆ๋‹ค [13,14] . ๊ธฐ์กด์˜ ์ด‰๊ฐ ์šด๋™ ํ•™์Šต ์—ฐ๊ตฌ ์ค‘, ์†Œ์ˆ˜์˜ ๋ฌธํ—Œ๋“ค๋งŒ์ด ์ด‰๊ฐ ๊ต์œก์˜ ํšจ๊ณผ๋ฅผ ์‹œ๊ฐ ๋˜๋Š” ์ฒญ๊ฐ ๊ต์œก๊ณผ ์ •๋Ÿ‰์ ์œผ๋กœ ๋น„๊ตํ•˜์˜€๋‹ค [6,8,10,[15][16][17] . ๊ด€๋ จ ์—ฐ๊ตฌ ์ค‘์—์„œ ์ง€์‹œ์™€ ๋ณด๊ฐ•์  ํ”ผ๋“œ๋ฐฑ์„ ํ•จ๊ป˜ ์‚ฌ์šฉํ•œ ์‚ฌ๋ก€๋Š” ์ผ๋ถ€ ๋ฌธํ—Œ์—์„œ ๋ฐœ๊ฒฌํ•  ์ˆ˜ ์žˆ์œผ๋‚˜ [9,10,18,19] , ๋นˆ๋„๋ฅผ ์กฐ์ ˆํ•˜๋Š” ๋ฐฉ์•ˆ์„ ๊ณ ๋ คํ•˜๊ณ  ์žˆ๋‹ค [26] .…”
unclassified